Short-time evaluation on intraocular scattering after implantable collamer lens implantation for correcting high myopia - Yu, Zhe (BMC Ophthalmol, 2020)
BACKGROUND: To compare the intraocular scattering before and after implantation of implantable collamer lens (ICL) V4c for correction of high myopia in a short term. METHODS: In this study, 38 eyes of 19 patients who underwent the implantation of ICL V4c were followed up for 3 months. Uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), objective scattering index (OSI), modulation transfer function cutoff frequency (MTF cutoff), strehl ratio (S/R), OV100%, OV20% and OV9% were measured pre- and postoperatively. Meantime, the Pseudophakic Dysphotopsia Questionnaire (PDQ) was scored to evaluate the subjective satisfaction of intraocular scattering pre- and postoperatively. RESULTS: The UCVA were − 0.02 ± 0.06, − 0.03 ± 0.07 and − 0.04 ± 0.07 logMAR at 1 week, 1 month and 3 months postoperatively which were significantly better than those preoperatively (P < 0.05). The BCVA were − 0.09 ± 0.09, − 0.09 ± 0.1 and − 0.1 ± 0.11 logMAR at 1 week, 1 month and 3 months after surgery, which were better than those before surgery significantly (t = 15.64, P < 0.05). The mean OSI were 2.37 ± 1.6, 1.63 ± 0.94, 1.5 ± 0.86 and 1.43 ± 1.05 preoperatively, 1 week, 1 month and 3 months postoperatively which was found significant difference (F = 12.92 P < 0.05). No significant differences were found in MTF cut off (F = 0.61, P = 0.62), S/R (F = 0.58, P = 0.36), OV100% (F = 0.966, P = 0.65), OV20% (F = 0.121, P = 0.96) and OV9% (F = 1.01, P = 0.30) between pre- and postoperatively. The PDQ results indicated that intraocular scattering reduced at 3 months after surgery significantly (P < 0.05). CONCLUSIONS: The ICL V4c implantation for correcting high myopia induced less intraocular scattering and visual disorder than spectacle correction.